Surgical Management of Elderly Patients (Springer International Publishing, 2018)
This volume offers a comprehensive and up-to-date overview of the major surgical procedures performed on elderly patients. With advancing age the conditions that require surgery normally increase in incidence, and today all surgeons around the globe can be considered "geriatric surgeons". The latest anesthesiological procedures, the technical improvements and an increased medical knowledge of the comorbities impact have brought extraordinary advances in this field, but this should not allow us to forget that a careful assessment of elderly patients is necessary before undertaking surgery, since also the simplest surgical procedures could alter the delicate psychophysical equilibrium of these "frail" patients. Introduced by a demographic panorama and analysis, the book describes the anesthesiological management, the preoperative assessment and preparation, the perioperative care, and hemostasis control connected with the main surgical pathologies: gastrointestinal, endocrine, neoplastic, vascular and hepato-biliary, as well with traumatic and non-traumatic emergencies. It will be an invaluable, easy-to-use resource for clinicians, researchers and trainees alike.